Campur kode etnik arab di kelurahan baru kabupaten tolitoli: kajian sosiolinguistik - Sudaryati, Sri (Universitas Madako Tolitoli, 2023)
This study discusses the forms, causes, and mixture of different types of Arabic ethnic codes in Kelurahan Baru, Tolitoli Regency. The questions of this research are: (1) How does the mixing of Arabic ethnic codes occur in the Baru Village, Tolitoli Regency? (2) What are the causes of the mixture of Arabic ethnic codes in Baru Village, Tolitoli Regency? (3 What are the types of mixture of Arab ethnic codes in the Baru Village, Tolitoli Regency? The purpose of this study is to (1) describe the form of the mixed Arabic ethnic code in Kelurahan Baru, Tolitoli Regency. (2) To elucidate the cause of the mixing of Arabic ethnic codes in Baru Village, Tolitoli Regency. (3) To investigate the different types of mixture of Arabic ethnic codes in the Baru Village, Tolitoli Regency. The research method used is qualitative research. Data were collected using five techniques: observation, listening, note-taking, and recording. The research subjects were Arabs living in Kelurahan Baru, Tolitoli Regency. The data analysis techniques used in this study include four phases: data collection, data reduction, data presentation, and conclusion validation. As a result, it was found that the mixed forms of Arabic ethnic codes in Kelurahan Baru, Tolitoli Regency, were in the form of basic words, affixes, repeated words, phrases, and clauses. Code-mixing arises from the habit of speakers to use their native language in their environment, resulting in relaxed conversation, socio-ethnic-cultural background, and third-party influences. The mixture of different types of Arab ethnic codes in the Baru Village, Tolitoli Regency, includes the mixture of exit codes and the mixture of internal codes.